The Form and Functioning of the Union of Czechoslovak Writers in the Late 1940s and Early 1950s in the Context of Czech Literature - Michal Bauer (eSamizdat)
The study examines the transformation of the Syndicate of Czech Writers into the Union of Czechoslovak Writers at the turn of the 1940s and 1950s, when the writers’ association turned into an ideological organisation fully dependent on official politics. The destruction of private publishing houses and the grouping into large, state-owned ones, is examined and analysed. The paradoxical role of writers and artists after 1948, i.e. to serve and to lead at the same time, is also discussed.